La explotación y disponibilidad de rana en el noroeste de México - Chávez, Ernesto A.; Valdez Ornelas, Víctor A.; Salgado Barragán, José (CIENCIA ergo-sum; Vol. 2 Núm. 3 (1995): CIENCIA ergo-sum (noviembre 1995-febrero 1996), 2017)
__